2019
DOI: 10.1186/s12870-019-1904-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals key factors in fruit ripening and rubbery texture caused by 1-MCP in papaya

Abstract: Background Ethylene promotes fruit ripening whereas 1-methylcyclopropene (1-MCP), a non-toxic antagonist of ethylene, delays fruit ripening via the inhibition of ethylene receptor. However, unsuitable 1-MCP treatment can cause fruit ripening disorders. Results In this study, we show that short-term 1-MCP treatment (400 nL•L − 1 , 2 h) significantly delays papaya fruit ripening with normal ripening characteristics. However, long-term 1-MCP trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 53 publications
4
36
0
Order By: Relevance
“…Moreover, firmness loss of apples in the treatment group rose significantly ( p < .05) compared with the control group. In previous experiments, different varieties of apples were harder than untreated apples after being treated with 1‐MCP (Fan, Blankenship, & Mattheis, 1999; Rupasinghe, Murr, Paliyath, & Skog, 2000; Watkins & Nock, 2005; Watkins, Nock, & Whitaker, 2000; Zhu et al, 2019). This may be due to that the carbon dioxide injured of fruit and the mechanical damage of fresh‐cut apples during processing and storage (Fawbush et al., 2008; Martino, Vizovitis, Botondi, Bellincontro, & Mencarelli, 2006).…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, firmness loss of apples in the treatment group rose significantly ( p < .05) compared with the control group. In previous experiments, different varieties of apples were harder than untreated apples after being treated with 1‐MCP (Fan, Blankenship, & Mattheis, 1999; Rupasinghe, Murr, Paliyath, & Skog, 2000; Watkins & Nock, 2005; Watkins, Nock, & Whitaker, 2000; Zhu et al, 2019). This may be due to that the carbon dioxide injured of fruit and the mechanical damage of fresh‐cut apples during processing and storage (Fawbush et al., 2008; Martino, Vizovitis, Botondi, Bellincontro, & Mencarelli, 2006).…”
Section: Resultsmentioning
confidence: 95%
“…In addition to ROS, other signaling pathways or molecules are also involved in plant senescence, including plant hormone transduction, ethylene, auxin, jasmonic acid and salicylic acid [39]. Plant hormones are indispensable in the regulation of fruit ripening and senescence, which control fruit color, sugar, flavor and aroma during ripening and senescence [40]. A previous study reported that ethylene and auxin play a major role in the ripening and senescence process of climacteric fruits [41].…”
Section: Plant Hormones Involved In Fruit Senescence At Postharvest Smentioning
confidence: 99%
“…Cell wall degradation is essential for fruit quality during fruit ripening and the senescence process [40]. The thickness and strength of the cell wall are key components for maintaining fruit firmness [48].…”
Section: Membrane and Cell Wall Component Changes During Postharvest mentioning
confidence: 99%
“…Besides ROS, other signaling pathways or molecular are also involved in plant senescence, including plant hormones transduction, ethylene, auxin, jasmonic acid and salicylic acid [39] . Plant hormones are indispensable to regulate fruit ripening and senescence, which controlled fruit color, sugar, flavor and aroma during ripening and senescence [40] . And previous study reported that ethylene and auxin were plays a major role in the ripening and senescence process of climacteric fruits [41] .…”
Section: Plant Hormones Involved In Fruit Senescence At Postharvest Smentioning
confidence: 99%
“…Cell wall degradation is essential for fruit quality during the fruit ripening and the senescence process [40] . The thickness and strength of cell wall are key components to maintenance the fruit firmness [48] .…”
Section: Membrane and Cell Wall Components Changes At Postharvest Stomentioning
confidence: 99%